6-m1 DEVELOPABLE SURFACES OF BIHARMONIC NEW TYPE b-SLANT HELICES ACCORDING TO BISHOP FRAME IN THE SOL SPACE Sol3 - Korpinar, T.; Turhan, E. (Turkic World Mathematical Soc, 2012)
In this paper, we study 6-m(1) developable surfaces of biharmonic new type 6-slant helix in the Sol(3). We characterize the 6-m(1) developable surfaces in terms of their Bishop curvatures. Finally, we fi nd out their explicit parametric equations in the Sol(3)
Keywords: New type 6-slant helix; Sol space; curvatures; 6-m(1) developable surface